2019
DOI: 10.1515/pac-2018-1106
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electrical impedance measurement in human skin assessment

Abstract: Structural and chemical alterations in living tissue are reflected in electrical impedance changes. However, due to the complexity of skin structure, the relation between electrical parameters and physiological/pathological conditions is difficult to establish. The impedance dispersion reflects the clinical status of the examined skin tissue and, therefore, it is frequently used in a non-invasive evaluation of exposing skin to various factors. The method has been used to assess the effect of the fish collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…It is less sensitive to the hydration status of the skin and can easily measure small changes in electrical resistance of hydrated skin, including at sites where micropores have been created [2]. Many studies have reported significant differences in skin impedance measured at various anatomical locations [24,25] and attributed these observations to differences in skin thickness, hydration level, and activity of sweat glands [25]. The results in our study showed that baseline skin impedance at the abdomen was significantly higher than at the upper arm across all subjects, and within the Latino and black self-identified racial/ethnic groups.…”
Section: Baseline Epidermal Propertiesmentioning
confidence: 99%
“…It is less sensitive to the hydration status of the skin and can easily measure small changes in electrical resistance of hydrated skin, including at sites where micropores have been created [2]. Many studies have reported significant differences in skin impedance measured at various anatomical locations [24,25] and attributed these observations to differences in skin thickness, hydration level, and activity of sweat glands [25]. The results in our study showed that baseline skin impedance at the abdomen was significantly higher than at the upper arm across all subjects, and within the Latino and black self-identified racial/ethnic groups.…”
Section: Baseline Epidermal Propertiesmentioning
confidence: 99%
“…It is often stressed that some of the collagen production methods may be expensive and cost-ineffective, which results in the limited use of collagen biomateri-als in the treatment of chronic wounds [13]. In our study we used collagen from the skin of freshwater fish (silver carp), which is inexpensive, easily available and characterized by good physicochemical properties [13,24,33,34,49]. Fish collagen has a relatively low molecular weight (less intermolecular crosslinking), which makes it possible to obtain a fully biologically active molecule in the form of helix.…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary analysis conducted in the group of 59 patients with VLUs we assessed the effect of the formulation on periwound skin and its ability to penetrate the corneal layer of the epidermis [49]. Electrical impedance measurements showed the improvement in the overall skin condition [49] while cutometry showed the improvement in skin elasticity and firmness after the use of collagen. In the placebo group, skin improvement was not significant [49,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncovering of collagen fibers in damaged tissues triggers a chain of cellular and biochemical reactions initiating the process of blood clotting and healing of tissues. This property of collagen is utilized in the process of homeostasis initiated by means of a collagen sponge applied on the wound [2][3][4].…”
Section: Introductionmentioning
confidence: 99%